Elimination of zirconium and niobium from uranium solution - Maroto, Alberto Jorge Gerardo; Flagenheimer, Juan G.; Peluffo, Carlos Alberto; Dupetit, G. A.; Kaufmann, Ferdy (Elsevier Sequoia, 1975)
Fil: Maroto, Alberto Jorge Gerardo Comisión Nacional de Energía Atómica; Argentina